Comparing the Effects of Subsidies on Target Goods - Markus Dertwinkel-Kalt; Christian Wey (CESifo GmbH, 2025)
We analyze the equilibrium effects of different subsidies on target goods under both perfectly competitive and monopolistic market structures. We concentrate our analysis on three particularly common forms of subsidies: (i) a per-unit subsidy, (ii) an ad valorem subsidy, and (iii) an "inversely related" subsidy, which increases as the price of the target good decreases. To evaluate the price effects of the subsidies, we rely on two criteria, an "equal-relief" criterion - which relies on a pass-through analysis - and a cost‑effectiveness criterion. Overall, the ad valorem subsidy always yields the strongest price-increasing effect, whereas an inversely related subsidy leads to the lowest price increase. Consequently, the ad valorem subsidy induces the largest output expansion under perfect competition, whereas the inversely related subsidy dominates the other subsidies in a monopoly under both criteria. Those findings are consistent with several empirical facts, such as observed price differences for green target goods across European countries.
Keywords: D04; D40; H20; 330; subsidies; target coods; equal-relief; pass through; cost effectiveness